Efektifitas Model Pembelajaran Perubahan Konseptual Untuk Mengatasi Miskonsepsi Fisika pada Siswa Kelas X Sman 1 Praya Barat Tahun Pelajaran 2012/2013 - Dwi Pebriyanti; Hairunnisyah Sahidu; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This research is a pre-experimental research with one group pretest Ã¢â¬â posttest design. The aim of this research is to know the efectivity of the conceptual changes model to solve the physics misconception of students in grade X SMAN 1 Praya Barat for academic year 2012/2013. The population is all of the students grade X SMAN 1 Praya Barat, it is 273 students and the sample is grade X.6, its 33 students that taking by using purposive sampling technique. The misconception data analized using gain value and N-gain. We get gain value (G) 17,5 % and N-gain <g> 0,65 with medium criteria. ItÃ¢â¬â¢s mean that the conceptual changes model is efective to solve the student misconception in grade X SMAN 1 Praya Barat with medium criteria.